Composite diaphragm and preparation method thereof, composite diaphragm preparation device and water electrolysis hydrogen production device

By adopting the preparation method of composite separator in alkaline electrolytic hydrogen production technology, the problems of insufficient stability and gas barrier properties of traditional separators are solved, and the electrolytic hydrogen production effect with high stability and low energy consumption is achieved.

CN119824476APending Publication Date: 2025-04-15JIANGSU TRINA GREEN HYDROGEN TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411971103.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Among the existing alkaline electrolytic hydrogen production technology, the traditional diaphragm has low stability, poor gas barrier performance, and complex process, which seriously affects the industrialization development of the diaphragm.

Method used

A composite separator is prepared using a method of preparing a cast film liquid and applying it to a porous support fabric. After initial phase transformation and secondary phase transformation, a composite separator with excellent stability and gas barrier properties are formed.

Benefits of technology

The high stability and excellent gas barrier properties of the composite diaphragm are achieved, the process is simplified, suitable for industrial production, and the energy consumption and chamber voltage are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824476A_ABST
    Figure CN119824476A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water electrolysis hydrogen production, in particular to a composite diaphragm and a preparation method thereof, a composite diaphragm preparation device and a water electrolysis hydrogen production device. The preparation method of the composite diaphragm provided by the invention comprises the following steps: coating the surface of a porous supporting fabric with a membrane casting solution, standing for initial phase transformation, and preparing an intermediate; the intermediate is immersed in a coagulating bath for secondary phase inversion, and a composite diaphragm is prepared; the membrane casting solution comprises the following components in parts by weight: 5-20 parts of a high-molecular polymer, 30-60 parts of inorganic hydrophilic particles and 15-65 parts of an organic solvent; the coating process parameters are as follows: the coating rate is 2.5 m / min-5m / min; the technological parameters of the standing are as follows: the temperature is 20-60 DEG C, the humidity is 30%-70%, and the standing time is 2s-1min. The preparation method is simple in process and suitable for industrial production, and the prepared composite diaphragm has excellent stability and gas barrier performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hydrogen production by electrolysis of water, and specifically to a composite diaphragm and a preparation method thereof, a composite diaphragm preparation device, and a hydrogen production device by electrolysis of water. Background Art

[0002] As an efficient, clean and environmentally friendly energy, hydrogen energy plays an important role in achieving carbon neutrality. Hydrogen production by water electrolysis is a highly promising green hydrogen production method. Currently, hydrogen production by water electrolysis mainly includes alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEM), solid oxide water electrolysis (SOEC) and anion exchange membrane water electrolysis (AEM). Among them, alkaline water electrolysis is the most mature technical route.

[0003] The diaphragm is the core component of hydrogen production by alkaline water electrolysis. On the one hand, it can prevent hydrogen and oxygen from mixing with each other to ensure the purity of hydrogen. On the other hand, it can allow ions in the solution to pass through to ensure the continuous electrolysis process and minimize the diaphragm resistance to reduce energy consumption. At present, the commercial diaphragms used for hydrogen production by alkaline water electrolysis mainly include asbestos diaphragms, polyphenylene sulfide (PPS) diaphragms, and composite diaphragms. Asbestos diaphragms have poor alkali corrosion resistance and poor gas barrier properties, so asbestos diaphragms are gradually eliminated. Although the high temperature resistance and alkali corrosion resistance of polyphenylene sulfide (PPS) diaphragms are better than asbestos diaphragms, their resistivity and gas barrier effects are still not ideal. Composite diaphragms are generally further specially formed on the support layer to form a composite diaphragm structure. However, the diaphragms prepared by traditional preparation methods are not stable, have poor gas barrier properties, and are complex processes, which seriously affect the industrial development of diaphragms. Summary of the invention

[0004] Based on this, the present application provides a composite diaphragm and a preparation method thereof, a composite diaphragm preparation device, and a water electrolysis hydrogen production device. The preparation method provided in the present application has a simple process, is suitable for industrial production, and can enable the prepared composite diaphragm to have both excellent stability and gas barrier properties.

[0005] In a first aspect of the present application, a method for preparing a composite membrane is provided, comprising the following steps:

[0006] A casting solution is prepared according to the following components in parts by weight: 5 to 20 parts of a high molecular polymer, 30 to 60 parts of inorganic hydrophilic particles, and 15 to 65 parts of an organic solvent;

[0007] The casting solution is applied to the surface of the porous support fabric, and after being allowed to stand for an initial phase transition, an intermediate is prepared;

[0008] Immersing the intermediate in a coagulation bath for secondary phase inversion to prepare the composite membrane;

[0009] The casting solution includes the following components in parts by weight: 5 to 20 parts of high molecular polymer, 30 to 60 parts of inorganic hydrophilic particles and 15 to 65 parts of organic solvent; the static process parameters include: temperature of 20°C to 60°C, humidity of 30% to 70%, and static time of 2s to 1min.

[0010] In one embodiment, in the step of immersing the intermediate in a coagulation bath for secondary phase transformation, the temperature of the secondary phase transformation is 10°C to 20°C.

[0011] In one embodiment, the coating process parameters include: a coating rate of 2.5 m / min to 5 m / min, a temperature of 20° C. to 60° C., and a humidity of 30% to 70%.

[0012] In one embodiment, the polymer has one or more of the following characteristics:

[0013] (1) The weight average molecular weight of the high molecular weight polymer is 50,000 to 75,000;

[0014] (2) The high molecular polymer includes one or more of polysulfone, polyethersulfone, polyetheretherketone, polyphenylene sulfide, sulfonated polyphenylene sulfide and sulfonated polysulfone.

[0015] In one embodiment, the high molecular weight polymer includes one or more of sulfonated polyphenylene sulfide and sulfonated polysulfone.

[0016] In one embodiment, the inorganic hydrophilic particles have one or more of the following characteristics:

[0017] (1) The inorganic hydrophilic particles include one or more of zirconium oxide, titanium oxide, silicon oxide, barium sulfate, lithium carbonate, aluminum oxide and calcium carbonate;

[0018] (2) The particle size of the inorganic hydrophilic particles is 20nm~100nm.

[0019] In one embodiment, the inorganic hydrophilic particles include yttrium-doped zirconium oxide.

[0020] In one embodiment, the casting solution further includes 0.1 to 5 parts of a pore-forming agent;

[0021] Optionally, the pore-forming agent includes one or more of polyvinylpyrrolidone, polyethylene glycol, sodium dodecyl sulfate, potassium hydroxide, lithium chloride and sodium chloride.

[0022] In one embodiment, the weight average molecular weight of the polyvinyl pyrrolidone is 50,000-60,000.

[0023] In one embodiment, the preparation method has one or more of the following characteristics:

[0024] (1) The coating thickness of the casting liquid on the porous support fabric is 100 μm to 500 μm;

[0025] (2) The coagulation bath comprises one or more of pure water, ethanol and N-methylpyrrolidone;

[0026] (3) The organic solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and triethyl phosphate;

[0027] (4) The material of the porous support fabric includes one or more of polyphenylene sulfide, polytetrafluoroethylene and polysulfone;

[0028] (5) The mesh number of the porous support fabric is 40-300 mesh.

[0029] In a second aspect of the present application, a composite membrane is provided, which is prepared by the preparation method described in any embodiment of the first aspect of the present application, and the composite membrane has one or more of the following characteristics:

[0030] (1) The bubble point pressure of the composite diaphragm is 2.6 Bar ~ 4.2 Bar;

[0031] (2) The surface resistance of the composite diaphragm is 0.08Ω·cm 2 ~0.18Ω·cm 2 ;

[0032] (3) The cell voltage of the composite diaphragm is 1.9V~2.05V.

[0033] In a third aspect of the present application, a composite membrane preparation device is provided, comprising: an unwinding mechanism, a coating module, a coagulation bath phase conversion mechanism and a winding mechanism sequentially arranged along a conveying direction of a porous support fabric;

[0034] The unwinding mechanism is used to place and transport the porous supporting fabric;

[0035] The coating module is disposed at the output end of the unwinding mechanism and is used to coat the casting liquid on at least one surface of the porous support fabric;

[0036] The coagulation bath phase transformation mechanism is arranged at the output end of the coating module, and the distance between the coating module and the coagulation bath phase transformation mechanism is 60 cm to 120 cm; it is used to allow the casting liquid coated on at least one surface of the porous support fabric to stand for initial phase transformation to prepare an intermediate;

[0037] The coagulation bath phase conversion mechanism is used to immerse the intermediate into a coagulation bath for secondary phase conversion to prepare a composite diaphragm;

[0038] The winding mechanism is arranged at the output end of the coagulation bath phase conversion mechanism.

[0039] In one embodiment, a cleaning mechanism is further provided between the coagulation bath conversion mechanism and the winding mechanism along the conveying direction of the porous supporting fabric;

[0040] The cleaning mechanism is used for cleaning the composite diaphragm.

[0041] In a fourth aspect of the present application, a device for producing hydrogen by electrolyzing water is provided, comprising a cathode electrode, an anode electrode and a diaphragm arranged between the cathode electrode and the anode electrode, wherein the diaphragm is the composite diaphragm described in the second aspect of the present application.

[0042] In one of the embodiments, the water electrolysis hydrogen production device further includes: an electrolyte filled in the water electrolysis hydrogen production device, wherein the electrolyte is an alkaline solution with a mass fraction of 25% to 35%.

[0043] The preparation method of the composite diaphragm provided in the present application has at least the following beneficial effects:

[0044] In the preparation method of the composite diaphragm provided in the present application, a casting solution containing specific components and weight fractions is used, so that the components in the casting solution have excellent compatibility, thereby making the coating process simpler. In addition, high molecular polymers and inorganic hydrophilic particles are selected in the casting solution, which makes the film layer formed on the porous support fabric have excellent stability, thereby reducing the shrinkage or deformation of the pores of the composite diaphragm caused by the increase in temperature.

[0045] In addition, the synergy of the initial phase transition treatment of the specific process parameters enables the high molecular polymer and inorganic hydrophilic particles in the casting solution to be initially arranged on the surface of the porous support fabric to form a preliminary pore structure; the formation of this preliminary pore structure enables the composite diaphragm to be better wetted by the electrolyte, thereby reducing the surface resistance of the composite diaphragm and ensuring that the composite diaphragm has excellent ionic conductivity. The good ionic conductivity of the composite diaphragm enables OH⁻ to efficiently migrate from the cathode to the anode, thereby reducing the cell voltage when the composite diaphragm is used in a water electrolysis hydrogen production device.

[0046] The intermediate is further immersed in a coagulation bath for secondary phase transformation, which can promote the exchange and removal of organic solvents in the casting solution, forming a denser finger-like or semi-finger-like structure, thereby increasing its bubble point pressure and ensuring the gas barrier performance of the composite diaphragm.

[0047] In summary, the preparation method of the composite diaphragm provided in the present application has a simple process, is suitable for industrial production, and can enable the prepared composite diaphragm to have low surface resistance, high bubble point pressure and excellent thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 A schematic diagram of the structure of the composite diaphragm preparation device provided in this application;

[0049] Figure 2 The test value of single electrolysis voltage of the composite diaphragm prepared in Example 1 of the present application at different current densities;

[0050] Figure 3 The composite diaphragm prepared in Examples 1 to 4 of the present application and the polyphenylene sulfide diaphragm of Comparative Example 1 are at 0.4 A / cm 2 Single electrolysis voltage test value at current density.

[0051] In the figure, 10 is an unwinding mechanism, 20 is a coating module, 30 is a coagulation bath phase conversion mechanism, 40 is a winding mechanism, 50 is a cleaning mechanism, 501 is a first cleaning tank, 502 is a second cleaning tank, and 503 is a third cleaning tank. DETAILED DESCRIPTION

[0052] The following is a further complete and clear description of the composite membrane and its preparation method, composite membrane preparation device, and water electrolysis hydrogen production device of the present application in conjunction with specific embodiments. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0053] In this application, "bubble point pressure" refers to the pressure at which the gas in the membrane begins to permeate at a certain temperature. A higher bubble point pressure indicates that the membrane has better gas barrier properties and can more effectively prevent gas permeation.

[0054] In this application, "surface resistance" refers to the resistance value per unit area of ​​the separator, which indicates the resistance of current passing through the separator. A lower surface resistance indicates a lower resistance of current passing through the separator.

[0055] In this application, "cell voltage" refers to the voltage of a single electrolytic cell unit (i.e., an electrolytic cell) when it is in operation. This voltage is the minimum potential difference required for the electrochemical reaction in the water electrolysis process, which reflects the efficiency and performance of the electrolytic cell. The cell voltage directly affects the energy efficiency of the water electrolysis process. A lower cell voltage means a higher energy conversion efficiency because less electrical energy is used to drive the electrolysis reaction.

[0056] The composite diaphragm usually includes a support layer and a modified layer formed on the surface of the support layer. The modified layer mainly includes high molecular polymers and inorganic nanoparticles. Since the modified layer combines the characteristics of organic and inorganic materials, it has good corrosion resistance.

[0057] At present, the preparation methods of related composite diaphragms include: (1) first preparing the composite diaphragm by phase inversion method, then attaching the polyvinyl alcohol hydrophilic modified coating solution to the composite diaphragm substrate, letting it stand in a coagulation bath, taking it out and drying it to obtain the composite diaphragm; although the composite diaphragm prepared by this method has a lower surface resistance, the stability of the prepared diaphragm is not high. (2) The diaphragm is etched by laser etching, and diaphragms with different pore sizes are obtained by designing different etching patterns and sizes; at the same time, by a reasonable etching channel shape, the appearance of the diaphragm stress concentration area can be effectively reduced, the mechanical properties of the diaphragm can be improved, and the surface resistance of the diaphragm can be reduced. However, this preparation method is relatively complicated and the cost is relatively high. (3) First modifying the support layer, and then preparing the composite diaphragm by phase inversion method. The stability of the diaphragm prepared by this preparation method is limited, and the maximum stability can only be maintained for 800 hours of operation.

[0058] In addition, the inventors of the present application have found based on rich experience and a large number of experiments that changes in small process parameters during the preparation of composite diaphragms will significantly affect the properties of the diaphragm. This is mainly because the pore structure of the composite diaphragm is closely related to its properties. When the pores of the composite diaphragm are larger, ions are easier to transmit and its surface resistance is reduced, but this is accompanied by a reduction in gas barrier properties. When the pores of the composite diaphragm are smaller, ion transmission is difficult at this time, but the gas barrier performance is excellent. Therefore, the pore structure of the composite diaphragm plays an important role in the properties of the composite diaphragm. During the preparation process, changes in small process parameters will affect the pore structure of the diaphragm.

[0059] Based on this, the first aspect of the present application provides a method for preparing a composite diaphragm, comprising the following steps:

[0060] S10, coating the casting solution on the surface of the porous support fabric, allowing it to stand for initial phase transformation, and then preparing an intermediate.

[0061] S20, immersing the intermediate in a coagulation bath for secondary phase transformation to prepare the composite diaphragm.

[0062] In one example, in step S10, the casting solution includes the following components in parts by weight: 5 to 20 parts of a high molecular polymer, 30 to 60 parts of inorganic hydrophilic particles, and 15 to 65 parts of an organic solvent.

[0063] It is understandable that in the present application casting solution, the weight parts of the high molecular polymer can be selected from any value between 5 and 20 parts. For example, the weight parts of the high molecular polymer include but are not limited to 5, 8, 10, 12, 14, 15, 18 or 20 parts, or within the range of any two of the above point values. The weight parts of the inorganic hydrophilic particles can be selected from any value between 30 and 60 parts. For example, the weight parts of the inorganic hydrophilic particles include but are not limited to 30, 35, 38, 40, 41, 42, 43, 45, 48, 50, 53, 55, 58 or 60 parts, or within the range of any two of the above point values. It is understandable that the weight parts of the organic solvent can be selected from any value between 15 and 65 parts. For example, the weight percentage of the organic solvent includes, but is not limited to, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 43 parts, 45 parts, 48 ​​parts, 50 parts, 53 parts, 55 parts, 58 parts, 60 parts, 63 parts or 65 parts, or within the range of any two of the above values. In one example, in step S10, the weight average molecular weight of the high molecular weight polymer is 50000-75000.

[0064] The casting liquid is coated on the surface of the porous support fabric, and after the initial phase transformation and the secondary phase transformation, the organic solvent in the casting liquid is volatilized, and the high molecular polymer and the inorganic hydrophilic particles form a modified layer on the surface of the porous support fabric. It can be understood that in the present application, the casting liquid is coated on both surfaces of the porous support fabric.

[0065] Therefore, the weight average molecular weight of the polymer plays an important role in ensuring the mechanical properties of the modified layer formed on the porous support fabric and the pore structure of the composite diaphragm. The present application defines the weight average molecular weight of the polymer. On the one hand, it can avoid the surface holes or unevenness that occur during the film forming process. This is conducive to balancing the porosity of the composite diaphragm, avoiding the decrease in gas barrier properties caused by excessively high porosity, and the limited ion conduction (increase in cell voltage) caused by excessively low porosity. On the other hand, it can avoid the disadvantages of coating and film forming difficulties caused by excessive viscosity of the casting liquid. It can be understood that in the present application, the weight average molecular weight of the polymer can be selected from any value between 50000 and 75000. For example, the weight average molecular weight of the polymer includes but is not limited to 50000, 53000, 55000, 58000, 60000, 62000, 65000, 68000, 70000, 72000 or 75000, or within the range of any two of the above point values.

[0066] In one example, in step S10, the high molecular polymer includes one or more of polysulfone, polyethersulfone, polyetheretherketone, polyphenylene sulfide, sulfonated polyphenylene sulfide and sulfonated polysulfone.

[0067] Furthermore, in step S10, the high molecular polymer includes one or more of sulfonated polyphenylene sulfide and sulfonated polysulfone.

[0068] The present application found that the high molecular polymers selected from sulfonated polyphenylene sulfide and sulfonated polysulfone can better cooperate with inorganic hydrophilic particles due to the additional introduction of sulfonic acid groups, so as to increase the hydrophilicity of the diaphragm, promote the penetration of electrolytes and ion conduction; and contribute to the efficient transmission of OH⁻, thereby reducing the cell voltage and improving the electrolysis efficiency.

[0069] In one example, in step S10, the process parameters for preparing the casting solution include: a mixing temperature of 40°C to 100°C, and a mixing speed of 100r / min to 150r / min. Ensuring the mixing temperature and mixing speed can allow the high molecular polymer and inorganic hydrophilic particles to be fully dissolved in the organic solvent to form a uniform casting solution; this is reflected in the fact that the pore structure of the modified layer formed by the casting solution on the composite diaphragm is more uniform, avoiding the generation of finger-shaped pores and semi-finger-shaped pores with larger pore sizes, ensuring the bubble point pressure, and making it have excellent gas barrier properties. Further, in step S10, the process parameters for preparing the casting solution include: a mixing temperature of 55°C to 65°C, and a mixing speed of 100r / min to 150r / min.

[0070] In one example, in step S10, the inorganic hydrophilic particles include one or more of zirconium oxide, titanium oxide, silicon oxide, barium sulfate, lithium carbonate, aluminum oxide and calcium carbonate.

[0071] In one example, in step S10, the particle size of the inorganic hydrophilic particles is 20 nm to 100 nm. For example, the particle size of the inorganic hydrophilic particles includes but is not limited to 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm, or within the range of any two of the above point values. By regulating the particle size of the inorganic hydrophilic particles, the prepared diaphragm can have a finger-like porous structure inside and present a hydrophilic / hydrophobic phase separation microstructure, which can effectively reduce the mass transfer resistance of the electrolyte and increase the OH - Conductivity.

[0072] Furthermore, in step S10, the inorganic hydrophilic particles include yttrium-doped zirconium oxide.

[0073] Yttrium-doped zirconia can endow the composite separator with excellent hydrophilicity to further promote electrolyte penetration and ion conduction.

[0074] In one example, in step S10, the casting solution also includes 0.1 to 5 parts of a pore-forming agent. The addition of a pore-forming agent can make the interior of the diaphragm have a through-hole structure, increase the porosity of the diaphragm, and thus improve the conductivity of OH⁻. By way of example, the weight percentage of the pore-forming agent includes but is not limited to 0.1 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 4.8 parts or 5 parts, or within the range of any two of the above point values.

[0075] The present application found that the addition of a pore-forming agent can reduce the thermodynamic stability of the casting solution system and change the viscosity of the casting solution to change the phase separation. It is understandable that the present application does not limit the type of pore-forming agent, as long as it can play a pore-forming role. In one example, in step S10, the pore-forming agent includes one or more of polyvinylpyrrolidone, polyethylene glycol, sodium dodecylsulfonate, potassium hydroxide, lithium chloride and sodium chloride.

[0076] Furthermore, in step S10, the weight average molecular weight of the polyvinyl pyrrolidone is 50,000 to 60,000. The present application finds that when polyvinyl pyrrolidone with a weight average molecular weight of 50,000 to 60,000 is used as a pore-forming agent, it can form uniform and controllable pores in the diaphragm after initial phase transition and secondary phase transition when it is compounded with a high molecular polymer and inorganic hydrophilic particles. These pores help to improve the permeability and ion conductivity of the electrolyte; in addition, the pores can also remain stable under long-term operating conditions, thereby giving the diaphragm excellent stability. And the weight average molecular weight of polyvinyl pyrrolidone can also give the diaphragm a certain flexibility to prevent the diaphragm from breaking and deforming during use, which can further increase the stability of the diaphragm.

[0077] For example, the weight average molecular weight of the polyvinyl pyrrolidone includes but is not limited to 50000, 51000, 52000, 53000, 54000, 55000, 56000, 57000, 58000, 59000 or 60000, or a range formed by any two of the above values.

[0078] In one example, in step S10, the organic solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and triethyl phosphate.

[0079] The porous support fabric is the matrix of the composite diaphragm. The material type and pore structure of the porous support fabric are conducive to gas permeation, especially in the process of hydrogen production by electrolysis of water, which can promote the effective separation and discharge of gas and improve the efficiency and safety of the system.

[0080] In one example, in step S10, the material of the porous support fabric includes one or more of polyphenylene sulfide, polytetrafluoroethylene and polysulfone.

[0081] In one example, in step S10, the mesh number of the porous support fabric is 40-300 mesh. For example, the mesh number of the porous support fabric includes but is not limited to 40 mesh, 60 mesh, 80 mesh, 100 mesh, 120 mesh, 140 mesh, 160 mesh, 180 mesh, 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh or 300 mesh, or a range formed by any two of the above point values.

[0082] An appropriate coating rate can ensure that the casting solution is evenly distributed on the porous support fabric to avoid local over-thickness or over-thinness. This helps to form a diaphragm with consistent thickness and improve its uniformity and consistency. In addition, the coating rate is also helpful for preparation and production. By regulating the position and distance of the coagulation bath and the coating area and moving the porous support fabric, the standing time can be regulated. In one example, in step S20, the process parameters of the coating include: a coating rate of 2.5m / min~5m / min. By way of example, the coating rate includes but is not limited to 2.5m / min, 2.8m / min, 3m / min, 3.1m / min, 3.2m / min, 3.5m / min, 4m / min, 4.5m / min or 5m / min, or within the range of any two of the above point values.

[0083] In one example, in step S10, the coating process parameters also include: temperature of 20°C to 60°C and humidity of 30% to 70%. In the present application, the coating temperature and humidity are static process parameters, which can effectively simplify the preparation conditions.

[0084] In one example, in step S10, the process parameters of the standing still include: temperature of 20°C to 60°C, humidity of 30% to 70%, and standing still time of 2s to 1min. In this application, "standing still" refers to the time after the casting solution is coated on the surface of the porous support fabric and exposed to air or oxygen atmosphere.

[0085] The present application found that the synergy of the static initial phase transformation treatment with specific coating rate and specific process parameters enables the high molecular polymer and inorganic hydrophilic particles in the casting solution to be initially arranged on the surface of the porous support fabric to form a preliminary pore structure; the formation of the preliminary pore structure enables the composite diaphragm to be better wetted by the electrolyte, thereby reducing the surface resistance of the composite diaphragm and ensuring that the composite diaphragm has excellent ionic conductivity. The good ionic conductivity of the composite diaphragm enables OH⁻ to efficiently migrate from the cathode to the anode, thereby reducing the cell voltage.

[0086] For example, the temperature of the standing temperature includes but is not limited to 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C, or within the range of any two of the above values. The humidity of the standing temperature includes but is not limited to 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, or within the range of any two of the above values. The standing time includes but is not limited to 2s, 10s, 20s, 30s, 40s, 50s or 60s, or within the range of any two of the above values. Controlling the process parameters in the standing step can avoid the shortcomings of insufficient initial phase transformation that may lead to an imperfect pore structure and affect the pore size distribution and porosity of the diaphragm; it can also avoid defects such as cracks and bubbles on the surface of the intermediate caused by long-term standing, and avoid the thick film layer after initial curing, which affects the ion conductivity.

[0087] In one example, in step S20, in the step of immersing the intermediate in a coagulation bath for secondary phase transformation, the temperature of the secondary phase transformation is 10° C. to 20° C. For example, the temperature of the secondary phase transformation includes but is not limited to 10° C., 12° C., 14° C., 16° C., 18° C. or 20° C.

[0088] In one example, in step S10, the coating thickness of the casting liquid on the porous support fabric is 100 μm to 500 μm. It can be understood that the coating thickness is the total thickness of the casting liquid coated on both sides of the porous support fabric. For example, the coating thickness includes but is not limited to 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm or 500 μm, or a range formed by any two of the above point values.

[0089] In one example, in step S20, the coagulation bath includes one or more of pure water, ethanol and N-methylpyrrolidone.

[0090] Furthermore, in step S20, the coagulation bath includes 3% to 15% by mass of N-methylpyrrolidone and 85% to 97% by mass of water.

[0091] Furthermore, in step S20, the coagulation bath includes 3% to 7% by mass of N-methylpyrrolidone and 93% to 97% by mass of water.

[0092] The coagulation bath can cause the polymer in the casting liquid to transform from a solution state to a solid state, forming a membrane with a specific pore structure. This process not only affects the porosity and pore size distribution of the membrane, but also has an important influence on the mechanical strength, hydrophilicity and surface properties of the membrane. By rationally selecting and controlling the composition, temperature and contact time of the coagulation bath, the comprehensive performance of the membrane can be optimized to meet the needs of specific applications. Among them, when the coagulation bath includes 3% to 7% N-methylpyrrolidone and 93% to 97% water by mass, when the casting liquid coated on the surface of the porous support fabric contacts the coagulation bath, the water in the coagulation bath will diffuse into the casting liquid, and the organic solvent in the casting liquid will diffuse into the coagulation bath. The mutual diffusion causes the polymer to phase separate, thereby forming a membrane with a specific porous structure. For example, the mass fraction of N-methylpyrrolidone included in the coagulation bath includes, but is not limited to, 3%, 4%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 6%, 6.5% or 7%, or a range consisting of any two of the above values. The mass fraction of water included in the coagulation bath includes, but is not limited to, 93%, 94%, 95%, 96% or 97%, or a range consisting of any two of the above values.

[0093] In one example, after step S20, the method further includes: cleaning the composite membrane. For example, the cleaning solution includes but is not limited to water and ethanol.

[0094] In one specific example, after step S20, the method further includes: washing the composite membrane three times with water, wherein the temperatures of the first water washing and the second water washing are independently selected from 15°C to 25°C, and the temperature of the third water washing is 30°C to 45°C.

[0095] A second aspect of the present application provides a composite diaphragm prepared by the preparation method described in any example of the first aspect of the present application.

[0096] In one example, the bubble point pressure of the composite membrane is 2.6 Bar to 4.2 Bar. For example, the bubble point pressure of the composite membrane includes but is not limited to 2.6 Bar, 2.8 Bar, 3 Bar, 3.2 Bar, 3.5 Bar, 3.8 Bar, 4 Bar, 4.2 Bar, 4.3 Bar or 4.5 Bar, or a range formed by any two of the above point values.

[0097] In one example, the surface resistance of the composite diaphragm is 0.08 Ω·cm 2 ~0.18Ω·cm 2 For example, the surface resistance of the composite membrane includes but is not limited to 0.08 Ω·cm 2 、0.09Ω·cm 2 , 0.1Ω·cm 2 、0.11Ω·cm 2 , 0.12Ω·cm 2 、0.13Ω·cm 2 、0.14Ω·cm 2 , 0.15Ω·cm 2 , 0.16Ω·cm 2 、0.17Ω·cm 2 or 0.18Ω·cm 2 , or within the range formed by any two of the above point values.

[0098] In one example, the cell voltage of the composite membrane is 1.9 V to 2.05 V. For example, the cell voltage of the composite membrane includes but is not limited to 1.91 V, 1.93 V, 1.95 V, 1.98 V, 2 V, 2.01 V, 2.02 V, 2.03 V, 2.04 V or 2.05 V, or a range formed by any two of the above values.

[0099] See also Figure 1 According to a third aspect of the present application, a composite membrane preparation device is provided, comprising: an unwinding mechanism 10, a coating module 20, a coagulation bath phase conversion mechanism 30 and a winding mechanism 40 which are sequentially arranged along the conveying direction of the porous support fabric.

[0100] The unwinding mechanism 10 is used to place and transport the porous supporting fabric.

[0101] The coating module 20 is disposed at the output end of the unwinding mechanism 10 and is used to coat the casting liquid on at least one surface of the porous supporting fabric.

[0102] The coagulation bath phase transformation mechanism 30 is arranged at the output end of the coating module 20, and the distance between the coating module 20 and the coagulation bath phase transformation mechanism 30 is 60cm~120cm; it is used to allow the casting liquid coated on at least one surface of the porous support fabric to stand for initial phase transformation to prepare an intermediate.

[0103] The coagulation bath phase conversion mechanism 30 is used to immerse the intermediate into a coagulation bath for secondary phase conversion to prepare a composite diaphragm.

[0104] The winding mechanism 40 is disposed at the output end of the coagulation bath phase conversion mechanism.

[0105] In the present application, the distance between the coating module 20 and the coagulation bath phase transformation mechanism 30 is set to 60cm~120cm. At this time, by adjusting the coating rate, that is, the transmission rate, the time for the initial phase transformation can be controlled. It can be understood that controlling the distance between the coating module 20 and the coagulation bath phase transformation mechanism 30 can make the casting liquid coated on at least one surface of the porous support fabric stand for the initial phase transformation. At this time, the composite diaphragm preparation device can be placed in a closed room environment with controlled temperature and humidity to regulate the temperature and humidity of the initial phase transformation.

[0106] In one example, a cleaning mechanism 50 is further provided between the coagulation bath conversion mechanism 30 and the winding mechanism 40 along the conveying direction of the porous support fabric;

[0107] The cleaning mechanism 50 is used to clean the composite diaphragm.

[0108] In one example, the cleaning mechanism 50 includes a first cleaning tank 501 , a second cleaning tank 502 , and a third cleaning tank 503 .

[0109] For example, the first cleaning tank 501 is used to place a solvent for performing the first cleaning and is suitable for performing the first cleaning.

[0110] The second cleaning tank 502 is used to place the solvent for the second cleaning and is suitable for the second cleaning.

[0111] The third cleaning tank 503 is used to place the solvent for the third cleaning and is suitable for the third cleaning.

[0112] Furthermore, the present application also provides a step of preparing a composite diaphragm using the composite diaphragm preparation device, comprising:

[0113] P100, take the porous support fabric and place it on the unwinding mechanism 10, set the conveying speed; convey the porous support fabric to the coating module 20 and fix it, introduce the casting liquid into the coating module 20, and coat the casting liquid on the surface of the porous support fabric.

[0114] P200, the distance between the coating module 20 and the coagulation bath phase transformation mechanism 30 is 60cm~120cm. During the process of transferring the porous support fabric coated with the casting liquid on both sides from the coating module 20 to the coagulation bath phase transformation mechanism 30 at a transfer speed, the fabric is left to stand, an initial phase transformation occurs, and an intermediate is prepared.

[0115] P300, immerse the intermediate into the coagulation bath phase conversion mechanism 30 for secondary phase change to prepare a composite membrane. Then the composite membrane is transferred to the first cleaning tank 501, the second cleaning tank and the third cleaning tank 503 for cleaning, and finally the composite membrane is rolled up by the winding mechanism 40 for storage.

[0116] In a fourth aspect of the present application, a device for producing hydrogen by electrolyzing water is provided, comprising a cathode electrode, an anode electrode and a diaphragm arranged between the cathode electrode and the anode electrode, wherein the diaphragm is the composite diaphragm described in the second aspect of the present application.

[0117] In one example, the water electrolysis hydrogen production device further includes: an electrolyte filled in the water electrolysis hydrogen production device, wherein the electrolyte is an alkaline solution with a mass fraction of 25% to 35%. The composite diaphragm provided in the present application has excellent stability in an alkaline environment, so it is suitable for electrolyzing alkaline water.

[0118] Specifically, an alkaline solution is selected as the electrolyte in the present application, wherein a voltage is applied to the water electrolysis hydrogen production device through a power supply, and hydroxide ions undergo oxidation reaction at the anode electrode to produce oxygen. The specific reaction includes: 4OH - - 4e - =O2+2H2O; at the cathode electrode, water molecules gain electrons and undergo a reduction reaction to produce hydrogen and hydroxide ions. At this time, the active components on the cathode electrode can promote the adsorption and desorption of hydrogen, thereby effectively improving the hydrogen evolution reaction. The specific reactions include: 2H2O+2e - = H2+2OH - .

[0119] The following further specific examples are provided to explain the present application in detail. It should also be understood that the following examples are only used to further explain the present application and cannot be understood as limiting the scope of protection of the present application. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present application belong to the scope of protection of the present application. The specific process parameters of the following embodiments are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not necessarily limited to the specific values ​​of the embodiments below.

[0120] Example 1

[0121] The composite membrane preparation device comprises: an unwinding mechanism 10, a coating module 20, a coagulation bath phase transformation mechanism 30, a cleaning mechanism 50 and a rewinding mechanism 40 which are sequentially arranged along the conveying direction of the porous support fabric. The unwinding mechanism 10 is used to place and transport the porous support fabric. The coating module 20 is arranged at the output end of the unwinding mechanism 10, and is used to apply the casting liquid to the two surfaces of the porous support fabric. The coagulation bath phase transformation mechanism 30 is arranged at the output end of the coating module 20, and the distance between the coating module 20 and the coagulation bath phase transformation mechanism 30 is 100 cm; it is used to make the casting liquid coated on at least one surface of the porous support fabric stand for initial phase transformation to prepare an intermediate. The coagulation bath phase transformation mechanism 30 is used to immerse the intermediate in a coagulation bath for secondary phase transformation to prepare a composite membrane. The rewinding mechanism 40 is arranged at the output end of the coagulation bath phase transformation mechanism. The cleaning mechanism 50 comprises a first cleaning tank 501, a second cleaning tank 502 and a third cleaning tank 503. The coagulation bath phase conversion mechanism 30 contains N-methylpyrrolidone:pure water in a mass ratio of 5:95; the first cleaning tank 501, the second cleaning tank 502 and the third cleaning tank 503 contain pure water.

[0122] Preparation steps of the composite diaphragm: (1) Preparation of casting solution: Weigh 14g of polysulfone (BASF S6010, weight average molecular weight of about 58,000~62,000), 42g of inorganic hydrophilic particles yttrium-doped zirconium oxide (particle size 20nm), 2g of polyvinyl pyrrolidone (58,000 medium molecular weight) as a pore-forming agent, and 42g of N-methylpyrrolidone as an organic solvent. Dissolve the above materials in a nitrogen environment at 60°C and at a speed of 300 r / min for 10 hours; stop stirring and let stand for degassing. (2) Take a clean polyphenylene sulfide support net (mesh number 220) and place it on the unwinding mechanism 10, and set the conveying speed to 3m / min; convey the polyphenylene sulfide support net to the coating module 20 for fixing, and introduce the casting liquid into the coating module 20, and coat the two sides of the polyphenylene sulfide support net with a total of 400 μm of casting liquid, wherein the coating process parameters include: ambient temperature 30°C, humidity 50%, and scraping the casting liquid at a speed of 3m / min. The distance between the coating module 20 and the solidification bath phase transformation mechanism 30 is 100cm. During the process of conveying the polyphenylene sulfide support net coated with the casting liquid on both sides from the coating module 20 to the solidification bath phase transformation mechanism 30 at a conveying speed of 3m / min, it is allowed to stand, and an initial phase transformation occurs to prepare an intermediate; wherein the standing process parameters include: ambient temperature 30°C, humidity 50%, and a standing time of 20s. (3) The intermediate is immersed in a coagulation bath phase transformation mechanism 30 for secondary phase change, wherein the coagulation bath contains N-methylpyrrolidone:pure water at a mass ratio of 5:95, and the temperature of the secondary phase transformation is 15°C, to prepare a composite membrane. The membrane is then transferred to the first cleaning tank 501 and the second cleaning tank, and washed twice with normal temperature water, and then transferred to the third cleaning tank 503, and washed once with pure water at 45°C, and finally the composite membrane is rolled up by the winding mechanism 40 for storage.

[0123] Example 2

[0124] Composite membrane preparation device: same as Example 1. The main difference is that the distance between the coating module 20 and the coagulation bath phase conversion mechanism 30 in Example 2 is 120 cm.

[0125] Preparation steps of the composite diaphragm: (1) Preparation of casting solution: Weigh 20g of polysulfone (BASF S6010), 30g of inorganic hydrophilic particles of yttrium-doped zirconium oxide (particle size 20nm), 5g of polyvinyl pyrrolidone (58,000 medium molecular weight) as a pore-forming agent, and 45g of N-methylpyrrolidone as an organic solvent. Dissolve the above materials in a nitrogen environment at 100°C with mechanical stirring at 500 r / min for 12 hours; stop stirring and let stand for degassing. (2) Take a clean polyphenylene sulfide support net (mesh number 200) and place it on the unwinding mechanism 10, and set the conveying speed to 2.5m / min; convey the polyphenylene sulfide support net to the coating module 20 for fixing, and introduce the casting liquid into the coating module 20, and coat the two sides of the polyphenylene sulfide support net with a total of 300 μm of casting liquid, wherein the coating process parameters include: ambient temperature 60°C, humidity 70%, and scraping the casting liquid at a speed of 2.5m / min. The distance between the coating module 20 and the solidification bath phase transformation mechanism 30 is 120cm. During the process of conveying the polyphenylene sulfide support net coated with the casting liquid on both sides from the coating module 20 to the solidification bath phase transformation mechanism 30 at a conveying speed of 2.5m / min, it is allowed to stand, and an initial phase transformation occurs to prepare an intermediate; wherein the standing process parameters include: ambient temperature 60°C, humidity 70%, and a standing time of 28.8s. (3) The intermediate is immersed in a coagulation bath phase transformation mechanism 30 for secondary phase change, wherein the coagulation bath contains pure water and the temperature of the secondary phase transformation is 20°C, to prepare a composite membrane. The membrane is then transferred to the first cleaning tank 501 and the second cleaning tank, and washed twice with normal temperature water, and then transferred to the third cleaning tank 503, and washed once with pure water at 40°C, and finally the composite membrane is rolled up by the winding mechanism 40 for storage.

[0126] Example 3

[0127] Composite membrane preparation device: same as Example 1. The main difference is that the distance between the coating module 20 and the coagulation bath phase conversion mechanism 30 in Example 3 is 60 cm.

[0128] Preparation steps of the composite diaphragm: (1) Preparation of casting solution: Weigh 12g of polysulfone (BASF S6010), 28g of inorganic hydrophilic particles of yttrium-doped zirconium oxide (particle size 100nm), 1.5g of polyvinyl pyrrolidone (58,000 medium molecular weight) as a pore-forming agent, and 58.5g of N-methylpyrrolidone as an organic solvent, and dissolve the above materials in a nitrogen environment at 50°C with mechanical stirring at 200 r / min for 12 hours; stop stirring and let stand for degassing. (2) Take a clean polyphenylene sulfide support net (mesh size 300) and place it on the unwinding mechanism 10, and set the conveying speed to 4m / min; convey the polyphenylene sulfide support net to the coating module 20 for fixing, and introduce the casting liquid into the coating module 20, and coat the two sides of the polyphenylene sulfide support net with a total of 250 μm of casting liquid, wherein the coating process parameters include: ambient temperature 30°C, humidity 40%, and scraping the casting liquid at a speed of 4m / min. The distance between the coating module 20 and the solidification bath phase transformation mechanism 30 is 60cm. During the process of conveying the polyphenylene sulfide support net coated with the casting liquid on both sides from the coating module 20 to the solidification bath phase transformation mechanism 30 at a conveying speed of 4m / min, it is allowed to stand, and an initial phase transformation occurs to prepare an intermediate; wherein the standing process parameters include: ambient temperature 30°C, humidity 40%, and a standing time of 9s. (3) The intermediate is immersed in a coagulation bath phase transformation mechanism 30 for secondary phase change, wherein the coagulation bath contains pure water and ethanol in a mass ratio of 9:1, and the temperature of the secondary phase transformation is 10°C, to prepare a composite membrane. The membrane is then transferred to the first cleaning tank 501 and the second cleaning tank, and washed twice with normal temperature water, and then transferred to the third cleaning tank 503, and washed once with pure water at 30°C, and finally the composite membrane is rolled up by the winding mechanism 40 for storage.

[0129] Example 4

[0130] Composite membrane preparation device: same as Example 1. The main difference is that the distance between the coating module 20 and the coagulation bath phase conversion mechanism 30 in Example 4 is 80 cm.

[0131] Preparation steps of the composite diaphragm: (1) Preparation of casting solution: Weigh 10g of polysulfone (BASF S6010), 40g of inorganic hydrophilic particles of yttrium-doped zirconium oxide (particle size 50nm), 4g of polyvinyl pyrrolidone (58,000 medium molecular weight) as a pore-forming agent, and 46g of N-methylpyrrolidone as an organic solvent, and dissolve the above materials in a nitrogen environment at 40°C with mechanical stirring at 400 r / min for 10 hours; stop stirring and let stand for degassing. (2) Take a clean polyphenylene sulfide support net (mesh number 240) and place it on the unwinding mechanism 10, and set the conveying speed to 3.5m / min; convey the polyphenylene sulfide support net to the coating module 20 for fixing, and introduce the casting liquid into the coating module 20, and coat the two sides of the polyphenylene sulfide support net with a total of 320 μm of casting liquid, wherein the coating process parameters include: ambient temperature 40°C, humidity 50%, and scraping the casting liquid at a speed of 3.5m / min. The distance between the coating module 20 and the solidification bath phase transformation mechanism 30 is 80cm. During the process of conveying the polyphenylene sulfide support net coated with the casting liquid on both sides from the coating module 20 to the solidification bath phase transformation mechanism 30 at a conveying speed of 3.5m / min, it is allowed to stand, and an initial phase transformation occurs to prepare an intermediate; wherein the standing process parameters include: ambient temperature 40°C, humidity 50%, and a standing time of about 14s. (3) The intermediate is immersed in a coagulation bath phase transformation mechanism 30 for secondary phase change, wherein the coagulation bath contains pure water and ethanol in a mass ratio of 9:1, and the temperature of the secondary phase transformation is 10°C, to prepare a composite membrane. The membrane is then transferred to the first cleaning tank 501 and the second cleaning tank, and washed twice with normal temperature water, and then transferred to the third cleaning tank 503, and washed once with pure water at 30°C, and finally the composite membrane is rolled up by the winding mechanism 40 for storage.

[0132] Example 5

[0133] Composite membrane preparation device: same as Example 1.

[0134] The preparation steps of the composite membrane are the same as those in Example 1. The main difference is that in Example 5, the pore-forming agent is polyethylene glycol of the same mass.

[0135] Example 6

[0136] Composite membrane preparation device: same as Example 1.

[0137] The preparation steps of the composite diaphragm are the same as those of Example 1. The main difference is that in Example 6, the pore-forming agent is potassium hydroxide of equal mass.

[0138] Example 7

[0139] Composite membrane preparation device: same as Example 1.

[0140] The preparation steps of the composite diaphragm are the same as those in Example 1. The main difference is that in Example 7, the pore-forming agent is sodium dodecyl sulfate of equal mass.

[0141] Example 8

[0142] Composite membrane preparation device: same as in Example 1. The coagulation bath phase conversion mechanism 30 of Example 8 contains pure water.

[0143] Preparation steps of the composite diaphragm: the same as in Example 1. The main difference is that in Example 8, pure water is used as the coagulation bath.

[0144] Example 9

[0145] Composite membrane preparation device: same as Example 1.

[0146] Preparation steps of the composite membrane: the same as in Example 1. The main difference is that the casting solution in Example 9 does not contain a pore-forming agent.

[0147] Example 10

[0148] Composite membrane preparation device: same as Example 1.

[0149] The preparation steps of the composite membrane are the same as those of Example 1. The main difference is that the high molecular weight polymer of the casting solution in Example 10 is selected from sulfonated polysulfone (14 g, weight average molecular weight of about 58,000-62,000).

[0150] Embodiment 11

[0151] Composite membrane preparation device: same as Example 1.

[0152] The preparation steps of the composite diaphragm are the same as those of Example 1. The main difference is that in Example 11, an equal mass of titanium dioxide (42 g) is selected as the inorganic hydrophilic particles in the casting solution.

[0153] Example 12

[0154] Composite membrane preparation device: same as Example 1.

[0155] Preparation steps of the composite diaphragm: the same as in Example 1. The main difference is that the temperature of the coagulation bath in Example 12 is 18°C.

[0156] Example 13

[0157] Composite membrane preparation device: same as Example 1.

[0158] The preparation steps of the composite diaphragm are the same as those in Example 1. The main difference is that the high molecular weight polymer in the casting solution of Example 10 is selected from polysulfone of equal weight (wherein, the weight average molecular weight of 20wt% polysulfone is 50000, and the weight average molecular weight of 80wt% polysulfone is 72000).

[0159] Comparative Example 1

[0160] In Comparative Example 1, a polyphenylene sulfide support mesh (mesh number 220) was selected as the diaphragm.

[0161] Comparative Example 2

[0162] Composite membrane preparation device: same as Example 1.

[0163] Preparation steps of the composite diaphragm: Same as Example 1. The main difference is that in step (3), the polyphenylene sulfide support net coated with the casting liquid on both sides is transported from the coating module 20 to the coagulation bath phase transformation mechanism 30 at a transmission speed of 0.1 m / min, and is allowed to stand to cause an initial phase transformation to prepare an intermediate; wherein the process parameters of the standing state include: an ambient temperature of 30° C., a humidity of 50%, and a standing time of 10 min.

[0164] Comparative Example 3

[0165] Composite membrane preparation device: same as Example 1.

[0166] Preparation steps of the composite diaphragm: Same as Example 1. The main difference is that in step (3), the polyphenylene sulfide support net coated with the casting liquid on both sides is transported from the coating module 20 to the coagulation bath phase transformation mechanism 30 at a transmission speed of 3.5 m / min, and is allowed to stand to undergo an initial phase transformation to prepare an intermediate; wherein the process parameters for the standing state include: an ambient temperature of 85° C., a humidity of 20%, and a standing time of about 10 s.

[0167] The single electrolysis voltage value of the composite diaphragm prepared in Example 1 was tested at different current densities. The corresponding test results are as follows: Figure 2 As shown. Figure 2 It can be seen that with the increase of current density, the overpotential of the diaphragm basically shows an increasing trend.

[0168] In addition, the test 0.4A / cm 2 The changes in the single electrolysis voltage values ​​of the composite diaphragms prepared in Examples 1 to 4 and the diaphragm of Comparative Example 1 under current density, and the corresponding test results are shown in Figure 3 As shown. Figure 3 It can be seen that at 0.4A / cm 2 The single electrolysis voltage value of the composite membranes of Examples 1 to 4 is about 1.91 V, while the single electrolysis voltage of the PPS membrane in Comparative Example 1 is 2.3 V. This indicates that the composite membranes of Examples 1 to 4 have low energy consumption characteristics.

[0169] The thickness, surface density, average pore size, and cell voltage of the diaphragm of each embodiment and comparative example were tested. The thickness was checked by a micrometer of related testing equipment, the surface resistance of the composite diaphragm was tested by Princeton PARSTAT equipment, and the bubble point pressure and average pore size were tested by a Bester bubble point instrument (pure water was used as the infiltration liquid when testing the average pore size). The cell voltage test was carried out using a multimeter, and the positive and negative connectors of the multimeter were inserted into the positive and negative ends of the electrolytic cell, and the cell body voltage test data was read after stabilization. The test conditions of the embodiments and comparative examples of the present application are 30wt% KOH solution and a temperature of 100°C. The relevant test results are detailed in Table 1.

[0170] Table 1 Test results of various embodiments and comparative examples

[0171]

[0172] The cell voltages of the diaphragms prepared in Comparative Examples 1 to 3 were all higher than those of Examples 1 to 13, indicating that the electric energy required for the electrochemical reaction during the electrolysis of water in the comparative examples was higher and the energy efficiency of the electrolysis of water was lower.

[0173] In Comparative Example 1, only polyphenylene sulfide support mesh is selected as the diaphragm, which has lower bubble point pressure, higher surface resistance, and higher cell voltage compared with Examples 1 to 13, which shows that the performance of the diaphragm of Comparative Example 1 is poor. In Comparative Examples 2 and 3, the process parameters such as the standing time, standing temperature, and standing humidity of the initial phase transition are adjusted. Among them, although the bubble point pressure value in Comparative Example 2 increases, its surface resistance and cell voltage are higher than those in Example 1, that is, the comprehensive performance of the diaphragm prepared in Comparative Example 2 is poor. Compared with Example 1, Comparative Example 3 has a lower bubble point pressure, a higher surface resistance, and a higher cell voltage; at this time, the performance of the composite diaphragm prepared in Comparative Example 3 is poor.

[0174] Example 1 and Example 5 to Example 7 are basically the same, and the main difference is that different pore-forming agents are selected. Among them, Example 1 uses polyvinyl pyrrolidone as a pore-forming agent, Example 5 uses polyethylene glycol as a pore-forming agent, Example 6 uses potassium hydroxide as a pore-forming agent, and Example 7 uses sodium dodecyl sulfonate as a pore-forming agent; from the test results in Table 1, it can be seen that the performance of the composite diaphragm prepared by using polyvinyl pyrrolidone as a pore-forming agent in Example 1 is the best. The difference between Example 9 and Example 1 is that Example 9 does not contain a pore-forming agent, and the performance of the composite diaphragm prepared by Example 9 is worse than that of Example 1.

[0175] Embodiment 1, Embodiment 8, and Embodiment 12 are basically the same, and the main difference is that the type of coagulation bath or the temperature of the coagulation bath is different. In Embodiment 8, pure water is used as the coagulation bath, which slightly reduces the performance of the composite membrane. In Embodiment 12, the coagulation bath temperature is slightly higher, which is conducive to the phase inversion process and is easy to form a macroporous structure, but its surface cortex is loose, which in turn causes the performance of the composite membrane to be slightly reduced.

[0176] Embodiment 1, Embodiment 10 and Embodiment 13 are basically the same, and the main difference is that the type of polymer or the molecular weight of the polymer is different. In Embodiment 10, the polymer is sulfonated polysulfone, and in Embodiment 13, the molecular weight of the polymer is adjusted, which will slightly reduce the performance of the composite membrane.

[0177] Example 1 and Example 11 are basically the same, the main difference is that different inorganic hydrophilic particles are selected, wherein Example 1 selects yttrium-doped zirconium oxide as inorganic hydrophilic particles, and Example 11 selects titanium oxide as inorganic hydrophilic particles. The performance of the composite diaphragm prepared in Example 11 is slightly worse than that in Example 1.

[0178] The stability of the diaphragm is the guarantee for testing the actual operating life of the diaphragm, and the stability of the diaphragm can be determined from the changing trends of the resistance and bubble point pressure under the thermal stability treatment state. Table 2 shows that in Example 1, by adding a suitable pore-forming agent, the ratio of zirconium oxide to polysulfone, optimizing the casting liquid ratio, selecting suitable film-forming processes such as air temperature and humidity values ​​and coagulation bath ratio, a diaphragm with excellent stability was prepared; and the performance in the stability test was far better than that of the composite diaphragm of international competitors.

[0179] Table 2 Stability test of composite diaphragms of Example 1 and Example 9 and international competitive products

[0180]

[0181] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0182] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solutions of the present application in detail, but cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description can be used to interpret the contents of the claims.

Claims

1. A method for preparing a composite diaphragm, characterized in that: The following steps are involved: The casting solution is applied to the surface of the porous support fabric, and after being allowed to stand for an initial phase transition, an intermediate is prepared; Immersing the intermediate in a coagulation bath for secondary phase inversion to prepare the composite membrane; The casting solution includes the following components in parts by weight: 5 to 20 parts of high molecular polymer, 30 to 60 parts of inorganic hydrophilic particles and 15 to 65 parts of organic solvent; the static process parameters include: temperature of 20°C to 60°C, humidity of 30% to 70%, and static time of 2s to 1min.

2. The method for preparing a composite diaphragm according to claim 1, characterized in that: In the step of immersing the intermediate into a coagulation bath for secondary phase transformation, the temperature of the secondary phase transformation is 10°C to 20°C.

3. The method for preparing the composite diaphragm according to claim 1, characterized in that: The coating process parameters include: coating rate of 2.5 m / min to 5 m / min, temperature of 20° C. to 60° C., and humidity of 30% to 70%.

4. The method for preparing a composite diaphragm according to any one of claims 1 to 3, characterized in that: The high molecular polymer includes one or more of polysulfone, polyethersulfone, polyetheretherketone, polyphenylene sulfide, sulfonated polyphenylene sulfide and sulfonated polysulfone.

5. The method for preparing the composite diaphragm according to claim 4, characterized in that: The polymer has one or more of the following characteristics: (1) The weight average molecular weight of the high molecular weight polymer is 50,000 to 75,000; (2) The high molecular polymer includes one or more of sulfonated polyphenylene sulfide and sulfonated polysulfone.

6. The method for preparing a composite diaphragm according to any one of claims 1 to 3, characterized in that: The inorganic hydrophilic particles have one or more of the following characteristics: (1) The inorganic hydrophilic particles include one or more of zirconium oxide, titanium oxide, silicon oxide, barium sulfate, lithium carbonate, aluminum oxide and calcium carbonate; (2) The particle size of the inorganic hydrophilic particles is 20nm~100nm.

7. The method for preparing a composite diaphragm according to claim 6, characterized in that: The inorganic hydrophilic particles include yttrium-doped zirconium oxide.

8. The method for preparing a composite diaphragm according to any one of claims 1 to 3, characterized in that: The casting solution also includes 0.1 to 5 parts of a pore-forming agent; Optionally, the pore-forming agent includes one or more of polyvinylpyrrolidone, polyethylene glycol, sodium dodecyl sulfate, potassium hydroxide, lithium chloride and sodium chloride.

9. The method for preparing a composite diaphragm according to claim 8, characterized in that: The weight average molecular weight of the polyvinyl pyrrolidone is 50,000-60,000.

10. The method for preparing a composite diaphragm according to any one of claims 1 to 3, characterized in that: The preparation method has one or more of the following characteristics: (1) The coating thickness of the casting liquid on the porous support fabric is 100 μm to 500 μm; (2) The coagulation bath comprises one or more of pure water, ethanol and N-methylpyrrolidone; (3) The organic solvent includes one or more of N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide and triethyl phosphate; (4) The material of the porous support fabric includes one or more of polyphenylene sulfide, polytetrafluoroethylene and polysulfone; (5) The mesh number of the porous support fabric is 40-300 mesh.

11. A composite diaphragm, characterized in that: Prepared by the preparation method according to any one of claims 1 to 10, the composite diaphragm has one or more of the following characteristics: (1) The bubble point pressure of the composite diaphragm is 2.6 Bar to 4.2 Bar; (2) The surface resistance of the composite diaphragm is 0.08Ω·cm 2 ~0.18Ω·cm 2 ; (3) The cell voltage of the composite diaphragm is 1.9V~2.05V.

12. A composite diaphragm preparation device, characterized in that: include: An unwinding mechanism, a coating module, a coagulation bath phase conversion mechanism and a winding mechanism are sequentially arranged along the conveying direction of the porous support fabric; The unwinding mechanism is used to place and transport the porous supporting fabric; The coating module is disposed at the output end of the unwinding mechanism and is used to coat the casting liquid on at least one surface of the porous support fabric; The coagulation bath phase transformation mechanism is arranged at the output end of the coating module, and the distance between the coating module and the coagulation bath phase transformation mechanism is 60 cm to 120 cm; it is used to allow the casting liquid coated on at least one surface of the porous support fabric to stand for initial phase transformation to prepare an intermediate; The coagulation bath phase conversion mechanism is used to immerse the intermediate into a coagulation bath for secondary phase conversion to prepare a composite diaphragm; The winding mechanism is arranged at the output end of the coagulation bath phase conversion mechanism.

13. The composite diaphragm preparation device according to claim 12, characterized in that: Along the conveying direction of the porous supporting fabric, a cleaning mechanism is also provided between the coagulation bath conversion mechanism and the winding mechanism; The cleaning mechanism is used for cleaning the composite diaphragm.

14. A hydrogen production device by electrolysis of water, characterized in that: It comprises a cathode electrode, an anode electrode and a diaphragm arranged between the cathode electrode and the anode electrode, wherein the diaphragm is the composite diaphragm according to claim 11.

15. The device for producing hydrogen by electrolysis of water according to claim 14, characterized in that: The water electrolysis hydrogen production device further includes: an electrolyte filled in the water electrolysis hydrogen production device, wherein the electrolyte is an alkaline solution with a mass fraction of 25% to 35%.